Power electronics converters, applications, and design - Mohan, Ned (John Wiley & Sons, 2003)
Offering step-by-step, in-depth coverage, the new Third Edition of Power Electronics: Converters, Applications, and Design provides a cohesive presentation of power electronics fundamentals for applications and design in the power range of 500 kW or less. The text describes a variety of practical and emerging power electronic converters made feasible by the new generation of power semiconductor devices.